Effect of high gamma radiation dosage and elevated temperature on the mechanical performance of sustainable alkali-activated composite as a cleaner product. (August 2021) - Ramadan, M.; Amin, M.S.; Waly, S.A.; Mohsen, Alaa
Abstract: This study aims to prepare novel and eco-sustainable alkali-activated cementitious products that resist fire and harmful radiation. The blends were prepared from partial replacement of slag with 0%, 10%, 20% and 30 wt% lead-rich sludge (LRS) followed by activation with 3% NaOH. The physico-mechanical properties as well as fire and radiation resistivity of the hardened composites were assessed. XRD, TGA/DTGA, FTIR and SEM/EDX analyses were adopted to explore the phase architecture and microstructure of various specimens. Superior mechanical performance was displayed by the composite accommodating 20% LRS; however, reasonable mechanical performance was delivered by the composite accommodating 30% LRS. The composite containing 30% LRS exhibited the greatest fire resistivity at 1000 °C. Impressive gamma-radiation resistivity was attained by the composite accommodating 10% LRS. SEM images affirmed the establishment of compacted/cross-linked microstructures for specimens exposed to a temperature of 250 °C or gamma ray irradiation at 2000 kGy. The proposed composites are recommended for secure utilization in the construction field. Highlights: Eco-sustainable alkali activated cementitious product was fabricated via adopting hazardous wastes. Appreciate mechanical performance was displayed by AAS-20LRS composite. Superior fire resistance was attained by AAS-30LRS composite at 1000 °C. Impressive gamma radiation resistivity was achieved by AAS-10LRS composite.